The Apotheosis of Greed in the Financial Markets in the Selected Feature Films - Borowski, Krzysztof (Journal of Finance and Financial Law, 2017)
Nowadays, in economic education, especially in Western Europe and the USA, it is becoming increasingly important to use feature films to illustrate: specific economic processes and phenomena, the behavior of investors in financial markets, as well as financial, social and psychological consequences of these behaviors. The paper discusses the fragments of selected films, foreign and Polish, which relate to the greed of investors in the financial markets or refer to their attitude to money. Fragments of these films, as well as other images can be used in the teaching process and during specialized courses in broadly understood finance.